Use of intracytoplasmic sperm injection (ICSI) in normospermic men may result in lower clinical pregnancy and live birth rates. (11th June 2019) - Sustar, Kylie; Rozen, Genia; Agresta, Franca; Polyakov, Alex
Abstract : Background: While intracytoplasmic sperm injection (ICSI) was developed for overcoming male infertility, it is increasingly being used for non‐male factor indications, without consensus regarding the safety and efficacy of this approach. Aims: To determine whether ICSI offers any benefit compared to standard in vitro fertilisation (IVF), in the setting of normal semen parameters. Materials and Methods: Retrospective analysis of reproductive outcomes in 3363 stimulated cycles (IVF = 1661; ICSI = 1702), in patients treated between 2009–2015, was performed. Selected couples had no male factor infertility. Couples with abnormal semen parameters (based on WHO 2010 guidelines), presence of anti‐sperm antibodies and low oocyte yield of ≤4 oocytes, were excluded. The outcomes analysed included: (1) fertilisation rate (FR); (2) clinical pregnancy rate (CPR); and (3) live birth rate (LBR), by method of fertilisation used (IVF vs ICSI) and controlling for significant confounders. Results: FR, CPR and LBR were significantly higher in the IVF group compared with ICSI (67.1% vs 62.3%, 23.06% vs 16.8%, 17.22% vs 13.2%, respectively). Pregnancy rate with ICSI was approximately 30% lower than with IVF, even when controlling for significant factors such as day of embryo transfer and number of embryos transferred. This translates to one less pregnancy in every 15 cycles where ICSI was used without clear indication. Conclusions: Our data suggest that ICSI may be detrimental to clinical outcomes and contributes to the wider understanding of use of ICSI in normospermic men.